2021
DOI: 10.48550/arxiv.2112.09314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-bound droplets in quasi-two-dimensional dipolar condensates

Abstract: We study the ground-state properties of self-bound dipolar droplets in quasi-two-dimensional geometry by using the Gaussian state theory. We show that there exist two quantum phases corresponding to the macroscopic squeezed vacuum and squeezed coherent states. We further show that the radial size versus atom number curve exhibits a double-dip structure, as a result of the multiple quantum phases. In particular, we find that the critical atom number for the self-bound droplets is determined by the quantum phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…More importantly, GST gives rise to the gapless excitation spectrum of condensates [36,42,43], which remedies the flaw of the Hartree-Fock-Bogoliubov theory. As to the stabilization mechanism of the dipolar and binary droplets, our studies showed that they were stablized by the three-body repulsion, instead of the quantum fluctuation [37][38][39]. In particular, we found two new macroscopic squeezed states in droplets, i.e.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…More importantly, GST gives rise to the gapless excitation spectrum of condensates [36,42,43], which remedies the flaw of the Hartree-Fock-Bogoliubov theory. As to the stabilization mechanism of the dipolar and binary droplets, our studies showed that they were stablized by the three-body repulsion, instead of the quantum fluctuation [37][38][39]. In particular, we found two new macroscopic squeezed states in droplets, i.e.…”
Section: Introductionmentioning
confidence: 76%
“…In a series of works [36][37][38][39][40], we studied the ground-state properties and the dynamics of the atomic condensates using the self-consistent Gaussian-state theory (GST) that takes account of the fluctuation at the Hartree-Fock-Bogoliubov level [41]. More importantly, GST gives rise to the gapless excitation spectrum of condensates [36,42,43], which remedies the flaw of the Hartree-Fock-Bogoliubov theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation